Evaluación de radiaciones no ionizantes generadas por las líneas de energía eléctrica de subtransmisión a 69 kv, en el eje de la subestación La Península - subestación Loreto ubicado en la ciudad de Ambato - Tiban Mangui, Ronny Daniel (2022)
An electrical power system consists of several elements from the generation to the final consumer, as there is a power flow that circulates through the transmission lines generates electric charges in motion, by this effect the electric field and the magnetic field (Electromagnetic Fields) are produced. The present study is referenced to the evaluation of non-ionizing radiation generated by 69 kV subtransmission power lines, obtaining information through a bibliographic compilation on the electric field and magnetic field in a transmission line. Consequently, this activity should take as a reference the levels exposed in the established regulations, where the electromagnetic fields will be identified and evaluated.